«Yo, para esto [soy], Hermosura: / para ver y ser vista»: Una propuesta sobre la actuación del personaje de Hermosura de El gran teatro del mundo de Calderón desde la iconología alegórica y la emblemática de los siglos xvi y xvii - Eduardo Paredes Ocampo (Criticón)
This study proposes a reconstruction of the performance of the character Hermosura in Calderón de la Barca’s play El gran teatro del mundo (1633-1635?). It aims to fill a gap in the criticism of Golden Age theater: the performance of actresses in sacramental plays is yet to be studied. Methodologically, this paper employs allegoric iconology, engravings, and emblems from the 16th and 17th centuries, such as Ripa’s Iconologia, Covarrubias’ Emblemas morales, and de Vos and Collaert’s Five Senses. From these documents, examples are selected that depict psychological states, feelings, and actions. Then, they are compared with the explicit and implicit stage directions related to the dramatic arc of Hermosura. The gestures, body movements, and proxemic relationships implicit in the engravings and emblems are applied to Calderón’s text to visually illustrate a possible staging of the character in the play. This analysis emphasizes the importance of in understanding the conflict of Hermosura in El gran teatro del mundo, specifically, and of the characters of Golden Age theater, in general.